Effects of leukocyte- and platelet-rich fibrin alone and combined with hyaluronic acid on early soft tissue healing after surgical extraction of impacted mandibular third molars: A prospective clinical study - GÖNÜL, ONUR (CHURCHILL LIVINGSTONE, 2019)
Purpose: In this prospective, randomized, double-blind, controlled study, we evaluated the effects of leukocyte- and platelet-rich fibrin (L-PRF) alone and combined with hyaluronic acid (HA) sponge on early healing of soft tissue after mandibular third molar (M3) surgery. Patients and methods: In total, 60 patients aged 18-30 (mean 22.3), 22 male and 38 female, were included in this study. After surgical extraction of the impacted M3, L-PRF was applied to the socket in the L-PRF group (n = 20), and a combination of L-PRF and HA was applied in the L-PRF + HA group (n = 20). Nothing was applied in the control group (n = 20). The primary outcome variable was healing score for the mucosa over the extraction socket on the 7th, 14th, and 21st days. Secondary outcome variables were frequencies of postoperative complications: hemorrhagic complications, alveolar osteitis (AO), and postoperative wound infection. Results: Mean healing scores for the mucosa on the 7th, 14th, and 21st days for both the L-PRF group and the L-PRF + HA group were significantly better than those for the control group. The ratio of alveolar osteitis for the control group was 1:20 and the ratio of postoperative wound infection for the control group was 1:20. There were no cases of alveolar osteitis or postoperative wound infection in the L-PRF and L-PRF + HA groups. No hemorrhagic complications were observed in this study. Conclusion: The results of this study suggest that L-PRF alone and when combined with HA can be an effective way to improve soft tissue healing, and could be used to prevent postoperative alveolar osteitis and infection after M3 surgery. Further studies with larger study groups are necessary. (C) 2018 European Association for Cranio-Maxillo-Facial Surgery. Published by Elsevier Ltd. All rights reserved.
Keywords: Impacted tooth; Hyaluronic acid; L-PRF; Wound healing; Soft tissue; Mucosa; HISTOLOGIC EVALUATIONS; POSTOPERATIVE PAIN; GROWTH-FACTORS; PLASMA; SURGERY; REGENERATION; PREVENTION; TRAMADOL; REMOVAL; SOCKETS